THE ACCOUNTANT’S AVERSION TO RISK WHEN CHOOSING ACCOUNTING POLICIES - Mariana GURĂU; Mariana Zenovia GRIGORE (Challenges of the Knowledge Society)
The accounting community is currently focusing on harmonizing accounting rules by creating a common accounting language at global level to increase the comparability and relevance of financial reporting information. The current requirements of reporting standards for presenting a true and fair image of the financial position have evolved from the practical necessities imposed by the activity of the economic entities. In this respect, it is necessary to reposition the regulations which define the concrete techniques for assessing the items presented in the balance sheet and in the income statement. In the accounting field, financial information is important for the users. It can be influenced by accounting policies, by the methods of valuation chosen by the specialist. This article is a point of view on the requirements of financial reporting, with particular emphasis on the valuation for the presentation of balance sheet and income statement. In Romania, in the absence of a tradition in this field, there is a risk aversion when it comes to evaluating for the purpose of presentation in the financial statements. We included in these paper an advisory study involving professional accountants and presented their point of view in the field of valuation at different times of the financial year. One of the objectives of these study is to clarify underline the importance to choose the accounting policies with no implications of taxes rules. The accountant have to understand that in our days accounting policies must be independent.